Contractor safety management (CRC Press, 2014)
"This book looks specifically at issues for health and safety management that arise in contracting relationships, bringing together a range of perspectives from different disciplines including legal, health and safety management, operational, contract and procurement management. By sharing lessons from both success and failure to identify critical issues in contractor safety management the book raises awareness of the complexity and importance of contractor safety management and to offer some guidance on how those critical issues might be addressed"-- Provided by publisher.
Keywords: Industrial safety -- Management.; Contracting out.; Industrial accidents -- Prevention.; Work environment.; elektronické knihy; electronic books